Eksistensi Sarung Tenun Muna pada Masyarakat di Desa Mabhodo Kecamatan Kontunaga Kabupaten Muna - Sri Wulandari; La Niampe; Rahmat Sewa Suraya (Jurusan Tradisi Lisan, Fakultas Ilmu Budaya, Univeritas Halu Oleo, 2023)
This study aims to analyse the form and meaning of the motifs of Muna woven sarongs in Mabhodo Village, Kontunaga District, Muna Regency. A qualitative descriptive method was used with data collection techniques through observation, interviews, documentation, and recording. Informants were selected purposively from traditional leaders and craftsmen. The results showed that Muna woven sarongs have bhotu, bhia-bhia, ledha, manggo-manggopa, samasili, kambeano banggai, lante-lante, bharalu, dhalima, panino toghe, kagholeno ghunteli motifs. These motifs have symbolic meanings that relate to rank, crown, class, and kabhantapi. Muna woven sarongs also have an attractive colour combination that reflects the three levels of Muna society.